2016
DOI: 10.1007/s00222-016-0655-7
|View full text |Cite
|
Sign up to set email alerts
|

Integer points on spheres and their orthogonal lattices

Abstract: Abstract. Linnik proved in the late 1950's the equidistribution of integer points on large spheres under a congruence condition. The congruence condition was lifted in 1988 by Duke (building on a break-through by Iwaniec) using completely different techniques. We conjecture that this equidistribution result also extends to the pairs consisting of a vector on the sphere and the shape of the lattice in its orthogonal complement. We use a joining result for higher rank diagonalizable actions to obtain this conjec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…There seems to be substantial scope for applying the theorems presented above to arithmetic questions. A concrete result in this direction by M. Aka, U. Shapira and the first named author [1] considers for all integer points (x, y, z) of the sphere x 2 + y 2 + z 2 = m both the normalized point m −1/2 (x, y, z) on the unit sphere S 2 and the shape of the lattice orthogonal to (x, y, z) in Z 3 , which corresponds to a point in PGL(2, Z)\H. Using Theorem 1.4 it is shown that these collections of pairs in S 2 ×PGL(2, Z)\H become equidistributed as m → ∞ along squarefree 1 integers, satisfying both m ≡ 0, 4, 7 mod 8 (a necessary and sufficient condition for existence of primitive integral points on the sphere of radius √ m) as well as an auxiliary condition of Linnik type-namely that (−m) is a quadratic residue modulo two distinct fixed primes.…”
mentioning
confidence: 93%
“…There seems to be substantial scope for applying the theorems presented above to arithmetic questions. A concrete result in this direction by M. Aka, U. Shapira and the first named author [1] considers for all integer points (x, y, z) of the sphere x 2 + y 2 + z 2 = m both the normalized point m −1/2 (x, y, z) on the unit sphere S 2 and the shape of the lattice orthogonal to (x, y, z) in Z 3 , which corresponds to a point in PGL(2, Z)\H. Using Theorem 1.4 it is shown that these collections of pairs in S 2 ×PGL(2, Z)\H become equidistributed as m → ∞ along squarefree 1 integers, satisfying both m ≡ 0, 4, 7 mod 8 (a necessary and sufficient condition for existence of primitive integral points on the sphere of radius √ m) as well as an auxiliary condition of Linnik type-namely that (−m) is a quadratic residue modulo two distinct fixed primes.…”
mentioning
confidence: 93%
“…There exists an analogous conjecture for k = 1, n − k ≥ 2 where one only considers the pairs (L, [L ⊥ (Z)]) (and similarly for n − k = 1, k ≥ 2). This has been studied extensively by the first named author with Einsiedler and Shapira in [AES16b,AES16a] where the conjecture is settled for n ≥ 6 (i.e. n − k ≥ 5), for n = 4, 5 under a weak congruence condition and for n = 3 under a stronger congruence condition on D. We remark that, as it is written, [AES16b,AES16a] treat only the case where Q is the sum of squares (that we will sometimes call the standard form), but the arguments carry over without major difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…This has been studied extensively by the first named author with Einsiedler and Shapira in [AES16b,AES16a] where the conjecture is settled for n ≥ 6 (i.e. n − k ≥ 5), for n = 4, 5 under a weak congruence condition and for n = 3 under a stronger congruence condition on D. We remark that, as it is written, [AES16b,AES16a] treat only the case where Q is the sum of squares (that we will sometimes call the standard form), but the arguments carry over without major difficulties. Using effective methods from homogeneous dynamics, Einsiedler, Rühr and Wirth [ERW19] proved an effective version of the conjecture when n = 4, 5 removing in particular all congruence conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present article aims to give an ergodic theoretic proof of Linnik's theorem using maximal entropy methods and following Einsiedler, Lindenstrauss, Michel and Venkatesh [11]. The motivation for such a proof originates from a refinement of Linnik's theorem by Aka, Einsiedler and Shapira in [3].…”
Section: Introductionmentioning
confidence: 99%